OPTIMALISASI PERSIAPAN RUANG MUAT GUNA MEMPERLANCAR PROSES BONGKAR MUAT DI MV. KAIROS JAYA 8 - Ridma Danty Kurniawan; Kurniawan Abadi; Arya Widiatmaja; Nelfi Erlinda; Rizal Rochmansyah (STKIP Subang, 2026)
Cargo hold preparation is an important factor in supporting the smooth implementation of cargo handling operations on board. Based on the results of Sea Practice conducted on MV. Kairos Jaya 8, it was found that cargo hold preparation had not been carried out optimally. The problems identified included delays in cleaning the cargo hold, lack of supervision from officers, inconsistent use of inspection checklists, and unstructured task distribution. This study aims to analyze the factors causing the suboptimal cargo hold preparation and to formulate improvement efforts that can be implemented. The research method used was descriptive qualitative, with data collected through direct observation, interviews, and documentation. The results show that the absence of a systematic Standard Operating Procedure (SOP), lack of coordination among crew members, and weak supervision were the main factors. Improvement efforts include developing and implementing SOPs, applying cargo hold readiness checklists, clarifying task distribution, and strengthening officer supervision.